Reported benefits of peer support group involvement by adults with hearing loss. (2nd January 2019) - Southall, Kenneth; Jennings, Mary Beth; Gagné, Jean-Pierre; Young, Jessica
Abstract: Objective: The purpose of this study was to better understand the benefits of self-help group involvement by adults with hearing loss. Design: A secondary content analysis of interview transcripts of participants from a previous study on the impact of stigma on help-seeking was carried out. Study sample: Ten members (aged 55–76 years) of self-help groups for persons with hearing loss in the United States of America and Canada participated in the interviews. Results: Three themes describing the benefits of self-help group participation emerged: (1) Practical and accessible information about hearing loss; (2) Social belonging leading to personal transformation; and (3) A new and mutually beneficial direction. Conclusions: The findings are discussed in relation to the "helper therapy principle", as well as group audiological rehabilitation.